Ultralow temperature resistant rubber and preparation method thereof
Through the combination of polyether polyurethane and fluorosilicone rubber and the combination of fine vulcanizing agent and filler, the problem of low-temperature resistant rubber is easily hardened and brittle broken in ultra-low temperature environments, achieving good elastic retention and tear resistance, and improving dynamic fatigue life and tensile strength.
Patent Information
- Application Number
- CN202510923414.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-04
- Publication Date
- 2025-08-22
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing low-temperature resistant rubbers are prone to hardening and brittle breaking in ultra-low temperature environments, and there are interface defects and microstructure uneven problems during vulcanization, making it difficult to meet the needs of ultra-low temperature elasticity maintenance and brittle breaking resistance at the same time.
A filling system of amino-terminated polyethylene glycol and precipitated white carbon black was prepared by a fluorosilic rubber with fluoromethyl group, combined with a vulcanizing agent of diisopropyl peroxide and bismaleimide, and an amino-terminated polyethylene glycol and a precipitated white carbon black were prepared by a staged kneading process.
It significantly improves the elastic retention ability and tear resistance of rubber at ultra-low temperatures, improves dynamic fatigue life and tensile strength, and solves the performance attenuation problem of rubber in the ultra-low temperature environment in the prior art.
Smart Images

Figure CN120519000A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of ultra-low temperature resistant rubber, and in particular to an ultra-low temperature resistant rubber and a preparation method thereof. Background Art
[0002] Ultra-low temperature resistant rubber has irreplaceable application value in aerospace seals, polar equipment elastic components and other fields. Its core performance requirement is to maintain good elasticity and mechanical properties in ultra-low temperature environments below -80°C. At present, the research and development of low-temperature resistant rubber in existing technologies mainly revolves around a single rubber matrix (such as polyurethane rubber or silicone rubber): polyurethane rubber exhibits a certain degree of elasticity at low temperatures due to the flexibility of the main chain ether bonds, but the interaction between the molecular chains is strong, and it is easy to harden at ultra-low temperatures due to the restricted movement of the chain segments; although silicone rubber has a low glass transition temperature, its side groups are mostly methyl or phenyl, and the molecular chains are prone to brittle fracture at low temperatures due to crystallization or enhanced interaction. It is difficult for a single rubber system to simultaneously meet the requirements of ultra-low temperature elasticity maintenance and brittle fracture resistance.
[0003] In terms of vulcanization system design, existing technologies mostly use single peroxide or sulfur as vulcanizing agents: the CC bond cross-linking network formed by peroxide vulcanization has limited strength and is prone to breakage due to local stress concentration at ultra-low temperatures; sulfur vulcanization easily forms polysulfide bonds, the bond energy decreases at low temperatures, and the network relaxation phenomenon is significant. Both single vulcanizing agent systems cannot effectively improve the tear resistance and dynamic fatigue life at ultra-low temperatures.
[0004] Regarding the optimization of the filling system, silica is widely used due to its high specific surface area and reinforcing effect. However, silica contains a large number of hydroxyl groups on its surface, and its interfacial compatibility with the non-polar rubber matrix is poor. In the existing technology, it is difficult to solve its agglomeration problem by simply mechanical mixing, resulting in the tensile strength and elongation at break of the filled rubber at ultra-low temperatures due to increased interface defects.
[0005] Traditional processing methods often employ a "one-step mixing" process, where all raw materials are added directly to an internal mixer. This process fails to precisely control the dispersion order and shear conditions of the main rubber and additives, leading to component segregation between the polyether polyurethane (polar) and fluorosilicone rubber (low-polarity) due to differences in compatibility. Furthermore, fillers like silica are prone to agglomeration due to insufficient local shearing, ultimately resulting in an uneven microstructure in the vulcanized rubber and significant fluctuations in ultra-low-temperature performance. Summary of the Invention
[0006] In view of the above-mentioned shortcomings of the prior art, an object of the present invention is to provide an ultra-low temperature resistant rubber and a preparation method thereof, so as to solve one or more problems in the prior art.
[0007] To achieve the above object, the technical solution of the present invention is as follows: Disclosed is an ultra-low temperature resistant rubber, comprising 45-55 parts of polyether polyurethane, 25-35 parts of fluorosilicone rubber with fluoromethyl side groups, 12-18 parts of amino-terminated polyethylene glycol, 35-45 parts of white carbon black, 2.5-3.5 parts of N-phenyl-N'-isopropyl-p-phenylenediamine, 2.0-3.0 parts of dicumyl peroxide, and 0.3-0.7 parts of bismaleimide.
[0008] Furthermore, the glass transition temperature of the polyether polyurethane is -68°C to -72°C, and the main chain contains ether bonds.
[0009] Furthermore, the glass transition temperature of the fluorosilicone rubber is -83°C to -87°C.
[0010] Furthermore, the molecular weight of the amino-terminated polyethylene glycol is 1800-2200.
[0011] Furthermore, the white carbon black is precipitated white carbon black with a specific surface area of 150-180m 2 / g.
[0012] To achieve a complete technical effect, the second technical solution of the present invention is a method for preparing ultra-low temperature resistant rubber. This method is nested and complementary to the first technical solution, which is an ultra-low temperature resistant rubber. The details are as follows: (1) Raw material pretreatment: polyether polyurethane is vacuum dried at 75-85℃ for 3.5-4.5h until the moisture content is ≤0.1%; fluorosilicone rubber is thinned 4-6 times on an open mill with a roller spacing of 0.4-0.6mm; (2) Premixing of main rubber: Add the pretreated polyether polyurethane and fluorosilicone rubber into an internal mixer at a mass ratio of (45-55): (25-35), first mix at 55-65°C and 25-35 r / min for 2.5-3.5 min, then heat to 75-85°C and mix at 45-55 r / min for 4.5-5.5 min to obtain a blend; (3) Mixing the additives: adding amino-terminated polyethylene glycol, white carbon black, and N-phenyl-N'-isopropyl-p-phenylenediamine to the blend in sequence, and mixing at 90-100°C and 35-45 r / min for 14-16 minutes; (4) Curing agent refining: add dicumyl peroxide and bismaleimide to the rubber compound after internal mixing, and pass it through the open mill at 70-80℃ with a roller spacing of 0.8-1.5mm for 4-6 times; (5) Compression vulcanization: The rubber compound after mixing is compression vulcanized at 160-170℃ and 14-16MPa for 19-21min to obtain ultra-low temperature resistant rubber.
[0013] Specifically, the initial crystallinity of the fluorosilicone rubber after thin-filming in step (1) is ≤2%.
[0014] Specifically, the order of adding materials in the banburying in step (3) is: blend → amino-terminated polyethylene glycol → white carbon black → N-phenyl-N'-isopropyl-p-phenylenediamine.
[0015] Specifically, the rotation speed of the front roller of the mixing mill in step (4) is 15-17 r / min, and the rotation speed of the rear roller is 17-19 r / min.
[0016] Specifically, in step (5), the positive vulcanization time t90 (the time to reach 90% vulcanization degree) of the compression vulcanization is 17-19 minutes, and the total compression vulcanization time is t90+1 minute to t90+3 minutes.
[0017] Compared with the prior art, the beneficial technical effects of the present invention are as follows: (1) By combining polyether polyurethane (main chain containing ether bonds) with fluorosilicone rubber with fluoromethyl side groups, a synergistic structure of "flexible main chain-low-temperature-resistant side groups" is formed. The ether bond main chain of the polyether polyurethane imparts mobility to the rubber molecular segments at low temperatures, preventing rigid fracture; the fluoromethyl side groups of the fluorosilicone rubber reduce the forces between the molecular chains through steric hindrance, further inhibiting low-temperature crystallization. The combined effect of the two significantly lowers the glass transition temperature of the rubber as a whole, achieving the ability to retain elasticity in ultra-low temperature environments (below -80°C), which is different from the defects of a single rubber system that is prone to hardening and brittle fracture at ultra-low temperatures.
[0018] (2) The combination of dicumyl peroxide and bismaleimide vulcanizers creates a composite vulcanization network characterized by "free radical crosslinking and bridging reinforcement." The peroxide vulcanizer (dicumyl peroxide) forms C-C crosslinks through free radical reactions, providing fundamental network strength. Bismaleimide, as a co-vulcanizer, has double bonds in its molecules that form bridges with rubber molecular chains and peroxide crosslinking points, filling network gaps and homogenizing crosslink density, avoiding localized over- or under-crosslinking. This ultimately improves the tear resistance and dynamic fatigue life of the vulcanized rubber at ultra-low temperatures, surpassing the low-temperature brittle fracture or network relaxation issues that can occur with a single vulcanizer system.
[0019] (3) The combination of amino-terminated polyethylene glycol and precipitated silica filler system realizes the synergistic dispersion mechanism of "polar plasticization-interface compatibility". The polar amino group of amino-terminated polyethylene glycol can form hydrogen bonds with the hydroxyl groups on the surface of silica, reducing the surface energy of silica; at the same time, its polyethylene glycol segment acts as a flexible spacer, which can be inserted between the rubber molecular chain and silica to reduce filler agglomeration. The combined effect of the two significantly improves the dispersion uniformity of silica in the rubber matrix, reduces the interface defects of the composite material, and thus improves the tensile strength and elongation at break at ultra-low temperatures. This is different from the problem of low-temperature mechanical performance degradation caused by uneven dispersion of traditional silica-filled rubber.
[0020] (IV) The combination of raw material pretreatment (polyether polyurethane drying and fluorosilicone rubber thin-pass) and a staged mixing process creates a "low-defect matrix - uniform dispersion" processing control path. Polyether polyurethane drying removes moisture, preventing bubble defects during vulcanization; fluorosilicone rubber thin-pass reduces initial crystallinity, improving its compatibility with polyether polyurethane; and staged mixing (first dispersing the main rubber at low temperature and low speed, then mixing the additives at higher temperatures and high speed) ensures uniform mixing of the components at the molecular level by controlling shear force and temperature gradients. This combined process ultimately ensures the uniformity of the vulcanizate's microstructure, reduces low-temperature performance fluctuations caused by processing defects, and is superior to the local component segregation problems that are common in traditional "one-step mixing" processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the preparation process of the ultra-low temperature resistant rubber in the present invention. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and exemplary explanations. It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not intended to limit the conditions for the implementation of the present invention. Therefore, they have no technical significance. Any modification of the structure, change in the proportion relationship or adjustment of the size should still fall within the scope of the technical content disclosed in the present invention without affecting the efficacy and purpose of the present invention.
[0023] Application Overview Ultra-low-temperature-resistant rubber, a key material in aerospace seals, polar equipment elastic components, and other fields, is required to maintain good elasticity and mechanical properties in ultra-low-temperature environments below -80°C. The current conventional technical approach in the industry for this field mainly revolves around the modification of a single rubber matrix (such as polyurethane or silicone rubber): polyurethane rubber relies on the flexibility of the main chain ether bonds to improve its low-temperature elasticity, but the interaction between the molecular chains is strong, and it is prone to hardening at ultra-low temperatures due to restricted segment motion; while silicone rubber has a low glass transition temperature, its side groups are mostly methyl or phenyl, and the molecular chains are prone to crystallization or enhanced interaction at low temperatures, leading to prominent brittle fracture problems. It is difficult for a single matrix to simultaneously maintain ultra-low-temperature elasticity and resist brittle fracture.
[0024] In the design of vulcanization systems, conventional solutions mostly use single peroxide or sulfur as vulcanizing agents: the CC bond cross-linking network formed by peroxide vulcanization has limited strength and is easily broken due to local stress concentration at ultra-low temperatures; sulfur vulcanization causes network relaxation due to the reduced low-temperature bond energy of polysulfide bonds. Both single vulcanizing agent systems cannot effectively improve ultra-low temperature tear resistance and dynamic fatigue life.
[0025] In order to optimize the filling system, the industry generally improves the mechanical properties by mechanically mixing reinforcing fillers such as silica. However, the hydroxyl groups on the surface of silica have poor interfacial compatibility with the non-polar rubber matrix. Simple mixing is difficult to solve the agglomeration problem, which can easily lead to a decrease in tensile strength and elongation at break due to increased interface defects at ultra-low temperatures.
[0026] Traditional processing methods often employ a "one-step mixing" process, where all raw materials are directly added to an internal mixer for mixing. This process fails to precisely control the dispersion order and shear conditions of the main rubber and additives. This can lead to component segregation due to differences in compatibility between polyether polyurethane (polar) and fluorosilicone rubber (low polarity). Furthermore, fillers like silica can agglomerate due to insufficient local shearing, ultimately resulting in an uneven microstructure in the vulcanized rubber and significant fluctuations in ultra-low temperature performance.
[0027] Comprehensive description The ultra-low-temperature-resistant rubber and preparation method provided by this invention aim to address the existing issues of rubber hardening, brittle fracture, and mechanical property degradation in ultra-low-temperature environments through optimized raw material composition and precise control of process parameters. The technical solutions of this invention are described in detail below, combining specific raw material compositions and preparation processes.
[0028] 1. Raw material composition The raw materials of the ultra-low temperature resistant rubber of the present invention include the following components in parts by mass: 45-55 parts of polyether polyurethane, 25-35 parts of fluorosilicone rubber with fluoromethyl side groups, 12-18 parts of amino-terminated polyethylene glycol, 35-45 parts of white carbon black, 2.5-3.5 parts of N-phenyl-N'-isopropyl-p-phenylenediamine, 2.0-3.0 parts of dicumyl peroxide, and 0.3-0.7 parts of bismaleimide.
[0029] Among them, polyether polyurethane is one of the main matrices, with a glass transition temperature of -68°C to -72°C. The main chain contains an ether bond structure, which gives the molecular chain flexible movement ability at low temperatures. Fluorosilicone rubber is another main matrix, with a side group of fluoromethyl and a glass transition temperature of -83°C to -87°C. The steric hindrance of the fluoromethyl group can reduce the force between the molecular chains and inhibit low-temperature crystallization. The molecular weight of amino-terminated polyethylene glycol is 1800-2200, and its polar amino group can form hydrogen bonds with the surface hydroxyl group of silica to improve the dispersion of the filler. Silica is prepared by precipitation method and has a specific surface area of 150-180m 2 / g, with high reinforcement; N-phenyl-N'-isopropyl-p-phenylenediamine is an antioxidant that can delay the oxidative aging of rubber during processing and use; dicumyl peroxide and bismaleimide serve as the main vulcanizing agent and co-vulcanizing agent, respectively, to synergistically build a uniform cross-linked network.
[0030] 2. Preparation Method The preparation process of the ultra-low temperature resistant rubber of the present invention includes five key steps: raw material pretreatment, main rubber premixing, auxiliary agent mixing, vulcanizing agent mixing and mold vulcanization. The specific operations are as follows: Raw material pretreatment Polyether polyurethane pretreatment: Place the polyether polyurethane in a vacuum drying oven at 75-85°C for 3.5-4.5 hours until the moisture content is ≤0.1%. This step removes moisture from the raw material to prevent bubbles from evaporating during the subsequent vulcanization process, which can affect the rubber's density.
[0031] Fluorosilicone rubber pretreatment: Place the fluorosilicone rubber in an open mill, set the roller spacing to 0.4-0.6mm, and thin-pass the rubber 4-6 times to reduce the initial crystallinity to ≤2%. The thin-pass operation destroys the initial crystalline structure of the fluorosilicone rubber through mechanical shearing, improving its compatibility with polyether polyurethane.
[0032] Main rubber premix Add the pretreated polyether polyurethane and fluorosilicone rubber into the internal mixer at a mass ratio of (45-55): (25-35) and mix in stages: The first stage: control the temperature of the internal mixer to 55-65℃, the speed to 25-35r / min, and mix for 2.5-3.5 minutes to achieve preliminary mixing of the two rubbers to avoid local overheating and degradation due to high temperature and high speed shear.
[0033] The second stage: raise the temperature to 75-85℃, increase the speed to 45-55r / min, and continue mixing for 4.5-5.5 minutes to promote the mutual penetration of molecular chains through higher shear force to form a uniform blend.
[0034] Additive mixing To the above blend, amino-terminated polyethylene glycol, silica, and N-phenyl-N'-isopropyl-p-phenylenediamine were sequentially added and kneaded at 90-100°C and 35-45 rpm for 14-16 minutes. The order of addition was based on the principle of "polar compatibilizer first, filler second": the polar groups of the amino-terminated polyethylene glycol preferentially bind to the hydroxyl groups on the silica surface, reducing its surface energy. The silica, already adsorbed with the compatibilizer, was then added, making it easier to disperse in the rubber matrix. Finally, the antioxidant was added to prevent premature aging that could affect subsequent vulcanization.
[0035] Vulcanizing agent refining Transfer the mixed rubber compound to an open mill, add dicumyl peroxide and bismaleimide, and pass the mixture through the mill 4-6 times at 70-80°C with a roll gap of 0.8-1.5mm. The front roll speed of the open mill is 15-17 rpm, and the rear roll speed is 17-19 rpm (speed ratio of approximately 1:1.06-1:1.27). The shear force generated by the speed ratio ensures that the vulcanizer is evenly dispersed in the rubber compound, while preventing premature decomposition of the vulcanizer due to excessive temperature.
[0036] Molding vulcanization The milled rubber compound is placed in a mold and compression-cured at 160-170°C and 14-16 MPa. The curing time is set between t90+1 minute and t90+3 minutes, based on the positive curing time t90 (the time it takes to reach 90% cure). The measured t90 value is 17-19 minutes (i.e., a total curing time of 18-22 minutes). This parameter range ensures a fully formed vulcanization network while preventing crosslink breakage caused by over-curing.
[0037] Through the above-mentioned raw material design and process control, the ultra-low temperature resistant rubber prepared by the present invention can still maintain good elasticity and mechanical properties in an environment below -80°C, and is suitable for scenarios with strict requirements on ultra-low temperature performance, such as aerospace seals and elastic components of polar equipment.
[0038] Experimental verification and performance analysis To verify the actual impact of the key parameters in this invention on the performance of ultra-low-temperature-resistant rubber, the following experimental plan was designed. Using the raw material components' weight percentages of polyether polyurethane (A), weight percentage of fluorosilicone rubber (B), and molecular weight of amino-terminated polyethylene glycol (C) as variables, the experiment compared the rubber properties under different parameter combinations to verify the rationality of the parameter ranges and the effectiveness of the preparation method.
[0039] 1. Experimental Design Test standard: Elongation at break (-80°C): Based on GB / T 528-2009 “Rubber, vulcanized or thermoplastic — Determination of tensile stress-strain properties”, using a low-temperature tensile testing machine, a test temperature of -80°C ± 2°C, and a tensile rate of 500 mm / min; Tear strength (-80℃): In accordance with GB / T 529-2008 "Rubber, vulcanized or thermoplastic — Determination of tear strength (trouser-shaped, right-angled and crescent-shaped test specimens)", using trouser-shaped specimens, the test temperature is -80℃±2℃; Dynamic fatigue life: According to ISO 4668:1991 “Rubber — Determination of dynamic properties — Compression fatigue heat generation”, using a compression fatigue testing machine, frequency of 10 Hz, compression strain of 20%, and the number of cycles until visible cracks appear on the specimen.
[0040] Variable settings: Variable A (weight parts of polyether polyurethane): limited to 45-55 parts, experimental values are 43, 45, 48, 50, 52, 55, and 57 parts; Variable B (mass parts of fluorosilicone rubber): limited to 25-35 parts, experimental values are 23, 25, 28, 30, 32, 35, and 37 parts; Variable C (molecular weight of amino-terminated polyethylene glycol): limited range 1800-2200, experimental values 1700, 1800, 1900, 2000, 2100, 2200, 2300.
[0041] Experimental group division: There are 10 groups of experiments in total, including: Conventional group (groups 1-5): variables A, B, and C are all within the specified range; Out-of-range group (6-9 groups): at least one variable is out of the limited range; Blank group (10 groups): using existing technology (single polyurethane rubber + traditional one-step mixing process).
[0042] Experimental conditions: Except for the variable, all other experimental groups remained consistent in terms of raw material components (40 parts of silica, 3.0 parts of antioxidant, 2.5+0.5 parts of vulcanizing agent combination), pretreatment process (polyether polyurethane drying conditions at 80°C×4h, 5 thin passes of fluorosilicone rubber), mixing parameters (staged mixing temperature of 55-85°C, rotation speed of 25-55 r / min), and vulcanization conditions (165°C×20min, 15 MPa).
[0043] 2. Experimental Results and Analysis The experimental results are recorded as follows (the data is the average of 3 parallel tests): Experimental group variable analysis table
[0044] [Note] Comprehensive score = elongation at break × 0.4 + tear strength × 0.3 + dynamic fatigue life × 0.2 (calculated after unit standardization) 3. Results and Discussion Experimental data show that: The performance of the conventional group (Groups 1-5) was significantly better than that of the out-of-range group (Groups 6-9): the conventional group had elongation at break ≥321%, tear strength ≥45kN / m, and dynamic fatigue life ≥1.22 million cycles, all higher than the out-of-range group (elongation at break ≤295%, tear strength ≤41kN / m, and dynamic fatigue life ≤1.06 million cycles), verifying the rationality of the variable limit range. The performance of the out-of-range group was better than that of the blank group: the elongation at break of the out-of-range group was ≥287%, the tear strength was ≥38kN / m, and the dynamic fatigue life was ≥980,000 times, all higher than those of the blank group (252%, 35kN / m, and 800,000 times), indicating that the preparation method of the present invention (multi-matrix blending + staged mixing) plays a fundamental role in improving performance. Non-linear relationship characteristics: The group with the highest comprehensive score in the conventional group was Group 3 (variables A=50 parts, B=30 parts, C=2000), rather than Group 1 or Group 5, which were not boundary values. This reflects the synergistic effect between the raw material components - when the ratio of polyether polyurethane to fluorosilicone rubber is close to 1.67:1 (50:30), the flexibility of the molecular chain and anti-crystallization properties reach the best balance; when the molecular weight of amino-terminated polyethylene glycol is 2000, the hydrogen bonding effect with silica is most stable, further verifying the scientific nature of the parameter range.
[0045] Through the above experiments, it can be clearly seen that the limited range of key parameters in the present invention has practical significance for improving ultra-low temperature performance, and the preparation method can effectively improve the comprehensive performance of rubber.
[0046] Weighted scoring analysis of experimental data and molecular-level mechanisms In the experimental data, the comprehensive score is calculated by weighting elongation at break (40%), tear strength (30%), and dynamic fatigue life (20%). Combining molecular structure and interaction mechanism, the underlying reasons for the performance trend can be analyzed as follows: 1. Molecular mechanism of the performance advantage of the conventional group (Groups 1-5) The variables of the conventional group (A = 45-55 parts, B = 25-35 parts, C = 1800-2200 parts) are all within a reasonable range. Its performance advantage comes from the synergistic effect of the three components at the molecular level: Blending balance of polyether polyurethane (A) and fluorosilicone rubber (B) The main chain of polyether polyurethane contains ether bonds (-O-), which have a long bond length (about 1.43Å) and a large bond angle (about 110°), giving the molecular chain flexible movement ability at low temperatures; the side group of fluorosilicone rubber is fluoromethyl (-CF3), and its strongly electronegative fluorine atoms weaken the van der Waals force between molecular chains (about 1.5-2.5kcal / mol) through the steric effect, inhibiting low-temperature crystallization (crystallization requires regular arrangement of molecular chains, and van der Waals force is the main driving force).
[0047] When A=50 parts and B=30 parts (ratio of about 1.67:1), the molecular chains of the two rubbers achieve the best balance of "flexibility-anti-crystallization": The ether bonds of polyether polyurethane provide sufficient freedom of chain segment movement (glass transition temperature Tg≈-70°C), preventing chain segment freezing at ultra-low temperatures; The fluoromethyl group of fluorosilicone rubber reduces the inter-molecular chain force to about 1.2 kcal / mol (lower than the 2.0 kcal / mol of pure polyurethane), lowering the critical crystallization temperature to below -85°C (the test temperature of -80°C did not trigger crystallization in the experiment).
[0048] This balance is directly reflected in the peak values of elongation at break (378.62%) and dynamic fatigue life (1.4825 million times) (Group 3). Since the chain segments are neither frozen nor crystallized, they can deform evenly during stretching, and stress dispersion during fatigue is more efficient.
[0049] Interfacial Regulation of Amino-Terminated Polyethylene Glycol (C) Amino-terminated polyethylene glycol (-NH2-(CH2CH2O) n -NH2) can form hydrogen bonds with the hydroxyl groups (-OH) on the surface of silica (bond energy is about 5-10kcal / mol), and its molecular chain (-(CH2CH2O) n -) acts as a "bridge" to connect the polar filler and the non-polar rubber matrix.
[0050] When the molecular weight of C is 2000 (n≈45), the molecular chain length is moderate: Too short (n<40, molecular weight<1800): cannot cover all hydroxyl groups on the surface of silica (the specific surface area of silica is 150-180m 2 / g, hydroxyl density is about 5 / nm 2 ), residual hydroxyl groups cause filler agglomeration (agglomerates become stress concentration points when their size is >5μm); Too long (n>50, molecular weight>2200): The molecular chains are severely entangled, reducing the compatibility with the rubber matrix (the polarity of polyether polyurethane is similar to that of polyethylene glycol, and the polarity of fluorosilicone rubber is lower. Excessively long chain segments are prone to migrate to polyurethane-rich areas, destroying uniformity).
[0051] Therefore, when C=2000, the dispersed particle size of silica is the smallest (about 2-3μm), the interface defects are the least, and the tear strength (54.71kN / m) reaches the highest value (Group 3). Because the interfacial bonding force that needs to be overcome during the tearing process is stronger, the crack propagation is more significantly hindered.
[0052] 2. Molecular reasons for performance degradation in the out-of-range group (groups 6-9) At least one variable in the out-of-range group exceeds the reasonable range, resulting in the destruction of molecular-level synergy: A=43 parts (below the lower limit): insufficient polyether polyurethane content, reduced ether bond number (every 2 parts reduction, ether bond density decreases by about 3%), segment flexibility decreases, some segments freeze at -80°C (Tg rises to -65°C), and elongation at break drops to 287.31% (Group 6); B=37 parts (higher than the upper limit): excessive fluorosilicone rubber, shortened distance between fluoromethyl groups (<0.3nm), enhanced induced dipole interaction between molecular chains (van der Waals force increased to 1.8kcal / mol), local crystallization (crystallinity of about 1.2%), rapid propagation of cracks along the crystalline region during tearing, and tear strength dropped to 40.12kN / m (Group 7); C=1700 or 2300 (out of range): When the molecular weight is too small, the hydroxyl coverage of the silica surface is only 70% (ideal is 90%), the size of the filler agglomerates increases to 4-5μm, and microcracks are easily caused at the edges of the agglomerates during dynamic fatigue (the fatigue life is reduced to 1.0591 million times, Group 8); when the molecular weight is large, the polyethylene glycol segment migrates to the polyurethane-rich area (the migration rate is about 15%), the interfacial bonding force between fluorosilicone rubber and silica is weakened (the hydrogen bond density is reduced by 20%), and the elongation at break is reduced to 292.58% (Group 9).
[0053] 3. The essential difference in performance disadvantage of the blank group (group 10) The blank group used a single polyurethane rubber + traditional one-step mixing process, which had two major defects at the molecular level: The chain segment movement of a single matrix is limited: the main chain of pure polyurethane contains a large number of urethane bonds (-NHCOO-), and the hydrogen bonding between molecular chains is strong (bond energy is about 15kcal / mol). The chain segments are completely frozen at -80℃ (Tg≈-55℃), and the elongation at break is only 252.64% (about 23% lower than the conventional group); Filler dispersion is extremely poor: One-step mixing cannot control the order of adding the compatibilizer and filler (the compatibilizer does not cover the silica hydroxyl group in advance). The silica agglomerate size is >8μm, the interface defect density is 3 times that of the conventional group, and the cracks extend directly along the edges of the agglomerates during tearing. The tear strength is only 35.19kN / m (about 35% lower than that of the conventional group).
[0054] in conclusion The nonlinear trend in the experimental data (the peak in the overall score occurs in Group 3, not in the borderline groups) is essentially the result of the synergistic interaction of multiple factors at the molecular level: the ratio of polyether polyurethane to fluorosilicone rubber determines the balance between chain flexibility and crystallization resistance, while the molecular weight of amino-terminated polyethylene glycol regulates the interfacial bonding strength between the filler and the matrix. The precise matching of these three factors within a reasonable range is the core mechanism for improving ultra-low-temperature performance; any variable outside this range will lead to a significant decline in performance through deterioration of intermolecular forces, chain segment mobility, or interfacial bonding strength.
[0055] Example Example 1 Preparation method: Raw material pretreatment: Take 45 parts of polyether polyurethane (glass transition temperature -70℃), place it in a vacuum drying oven, and dry it at 80℃ for 4 hours to a moisture content of 0.08%; Take 25 parts of fluorosilicone rubber with fluoromethyl side groups (glass transition temperature -85°C), put it into an open mill, set the roller spacing to 0.5 mm, and pass it through the mill 5 times to reduce the initial crystallinity to 1.8%.
[0056] Main rubber premix: The pretreated polyether polyurethane and fluorosilicone rubber were added to the internal mixer. In the first stage, the temperature was controlled at 60°C and the speed was 30 r / min, and the mixing was carried out for 3 minutes. In the second stage, the temperature was raised to 80°C and the speed was 50 r / min, and the mixing was continued for 5 minutes to form a uniform blend.
[0057] Mixing of additives: 15 parts (by mass) of amino-terminated polyethylene glycol with a molecular weight of 1800, 40 parts of white carbon black (specific surface area 160m 2 / g), 3.0 parts of N-phenyl-N'-isopropyl-p-phenylenediamine, and banburying at 95°C and 40r / min for 15 minutes.
[0058] Vulcanizing agent refining: The rubber compound was transferred to an open mixing mill, 2.5 parts of dicumyl peroxide and 0.5 parts of bismaleimide were added, and the mixture was passed through the mixing mill 5 times at 75°C with a roller spacing of 1.0 mm (front roller speed 16 r / min, rear roller speed 18 r / min).
[0059] Compression vulcanization: The rubber compound was placed in a mold and compression-vulcanized at 165°C and 15 MPa for 20 minutes (the measured positive vulcanization time t90 was 19 minutes, and the total vulcanization time was t90+1 minute) to obtain ultra-low temperature resistant rubber.
[0060] Example 2 Preparation method (only variables are adjusted, the rest of the steps are the same as in Example 1): Raw material pretreatment: 48 parts of polyether polyurethane (glass transition temperature -70°C), 28 parts of fluorosilicone rubber (glass transition temperature -85°C); Auxiliary agent mixing: add 15 parts of 1900 molecular weight amino-terminated polyethylene glycol; The remaining step parameters (drying temperature 80°C×4h, mixing temperature / speed / time, open mixing conditions, and vulcanization conditions) are exactly the same as those in Example 1.
[0061] Example 3 Preparation method (only variables are adjusted, the rest of the steps are the same as in Example 1): Raw material pretreatment: 50 parts of polyether polyurethane (glass transition temperature -70°C), 30 parts of fluorosilicone rubber (glass transition temperature -85°C); Auxiliary agent mixing: add 15 parts of 2000 molecular weight amino-terminated polyethylene glycol; The remaining step parameters are exactly the same as those in Example 1.
[0062] Example 4 Preparation method (only variables are adjusted, the rest of the steps are the same as in Example 1): Raw material pretreatment: 52 parts polyether polyurethane (glass transition temperature -70°C), 32 parts fluorosilicone rubber (glass transition temperature -85°C); Auxiliary agent mixing: add 15 parts of 2100 molecular weight amino-terminated polyethylene glycol; The remaining step parameters are exactly the same as those in Example 1.
[0063] Example 5 Preparation method (only variables are adjusted, the rest of the steps are the same as in Example 1): Raw material pretreatment: 55 parts of polyether polyurethane (glass transition temperature -70°C), 35 parts of fluorosilicone rubber (glass transition temperature -85°C); Auxiliary agent mixing: add 15 parts of 2200 molecular weight amino-terminated polyethylene glycol; The remaining step parameters are exactly the same as those in Example 1.
[0064] Example 6 Preparation method (only variables are adjusted, the rest of the steps are the same as in Example 1): Raw material pretreatment: 43 parts polyether polyurethane (glass transition temperature -70°C), 25 parts fluorosilicone rubber (glass transition temperature -85°C); Auxiliary agent mixing: add 15 parts of 1800 molecular weight amino-terminated polyethylene glycol; The remaining step parameters are exactly the same as those in Example 1.
[0065] Example 7 Preparation method (only variables are adjusted, the rest of the steps are the same as in Example 1): Raw material pretreatment: 55 parts polyether polyurethane (glass transition temperature -70°C), 37 parts fluorosilicone rubber (glass transition temperature -85°C); Auxiliary agent mixing: add 15 parts of 2200 molecular weight amino-terminated polyethylene glycol; The remaining step parameters are exactly the same as those in Example 1.
[0066] Example 8 Preparation method (only variables are adjusted, the rest of the steps are the same as in Example 1): Raw material pretreatment: 50 parts of polyether polyurethane (glass transition temperature -70°C), 30 parts of fluorosilicone rubber (glass transition temperature -85°C); Auxiliary agent mixing: add 15 parts of 1700 molecular weight amino-terminated polyethylene glycol; The remaining step parameters are exactly the same as those in Example 1.
[0067] Example 9 Preparation method (only variables are adjusted, the rest of the steps are the same as in Example 1): Raw material pretreatment: 50 parts of polyether polyurethane (glass transition temperature -70°C), 30 parts of fluorosilicone rubber (glass transition temperature -85°C); Auxiliary agent mixing: add 15 parts of 2300 molecular weight amino-terminated polyethylene glycol; The remaining step parameters are exactly the same as those in Example 1.
[0068] Example 10 (blank control group) Preparation method (using existing technology): Raw material pretreatment: Take 100 parts of single polyurethane rubber (glass transition temperature -55°C), place it in a vacuum drying oven, and dry it at 80°C for 4 hours to a moisture content of 0.08% (without adding fluorosilicone rubber).
[0069] One-step mixing: Add the dried polyurethane rubber into the internal mixer and directly add 40 parts of white carbon black (specific surface area 160m 2 / g), 3.0 parts of N-phenyl-N'-isopropyl-p-phenylenediamine, and 2.5 parts of dicumyl peroxide, and kneaded at 95°C and 40 r / min for 20 minutes (without staged mixing and without adding amino-terminated polyethylene glycol).
[0070] Compression vulcanization: The rubber compound was placed in a mold and vulcanized at 165°C and 15 MPa for 20 minutes to produce a comparative rubber.
[0071] Specific working process After the polyether polyurethane is vacuum dried to a low moisture content, it is put into an open mill together with fluorosilicone rubber for thin mixing to reduce the initial crystallinity; the two treated rubbers are transferred to an internal mixer, first preliminarily mixed at a low temperature and speed, and then the temperature is increased to accelerate the mixing to form a uniform blend; amino-terminated polyethylene glycol, white carbon black and antioxidant are added to the blend in sequence and continue to be mixed; after completion, the rubber compound is transferred to an open mill, and a vulcanizing agent combination is added for thin mixing; finally, the rubber compound is placed in a mold for compression vulcanization to produce ultra-low temperature resistant rubber.
[0072] The various technical features described in the above exemplary embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the various technical features in the above exemplary embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
Claims
1. A super low temperature resistant rubber, characterized by: The invention comprises 45-55 parts of polyether polyurethane, 25-35 parts of fluorosilicone rubber with fluoromethyl side groups, 12-18 parts of amino-terminated polyethylene glycol, 35-45 parts of white carbon black, 2.5-3.5 parts of N-phenyl-N'-isopropyl-p-phenylenediamine, 2.0-3.0 parts of dicumyl peroxide and 0.3-0.7 parts of bismaleimide.
2. The ultra-low temperature resistant rubber according to claim 1, characterized in that: The polyether polyurethane has a glass transition temperature of -68°C to -72°C, and a main chain contains an ether bond.
3. The ultra-low temperature resistant rubber according to claim 1, characterized in that: The glass transition temperature of the fluorosilicone rubber is -83°C to -87°C.
4. The ultra-low temperature resistant rubber according to claim 1, characterized in that: The molecular weight of the amino-terminated polyethylene glycol is 1800-2200.
5. The ultra-low temperature resistant rubber according to claim 1, characterized in that: The white carbon black is precipitated white carbon black with a specific surface area of 150-180m 2 / g.
6. A method for preparing ultra-low temperature resistant rubber, based on the ultra-low temperature resistant rubber according to any one of claims 1 to 5, characterized in that: (1) Raw material pretreatment: polyether polyurethane is vacuum dried at 75-85℃ for 3.5-4.5h until the moisture content is ≤0.1%; fluorosilicone rubber is thinned 4-6 times on an open mill with a roller spacing of 0.4-0.6mm; (2) Premixing of main rubber: Add the pretreated polyether polyurethane and fluorosilicone rubber into an internal mixer at a mass ratio of (45-55): (25-35), first mix at 55-65°C and 25-35 r / min for 2.5-3.5 min, then heat to 75-85°C and mix at 45-55 r / min for 4.5-5.5 min to obtain a blend; (3) Mixing the additives: adding amino-terminated polyethylene glycol, white carbon black, and N-phenyl-N'-isopropyl-p-phenylenediamine to the blend in sequence, and mixing at 90-100°C and 35-45 r / min for 14-16 minutes; (4) Curing agent refining: add dicumyl peroxide and bismaleimide to the rubber compound after internal mixing, and pass it through the open mill at 70-80℃ with a roller spacing of 0.8-1.5mm for 4-6 times; (5) Compression vulcanization: The rubber compound after mixing is compression vulcanized at 160-170℃ and 14-16MPa for 19-21min to obtain ultra-low temperature resistant rubber.
7. The method for preparing ultra-low temperature resistant rubber according to claim 6, wherein: The initial crystallinity of the fluorosilicone rubber after thin-filming in step (1) is ≤2%.
8. The method for preparing ultra-low temperature resistant rubber according to claim 6, wherein: The order of adding materials in the banburying in step (3) is: blend → amino-terminated polyethylene glycol → white carbon black → N-phenyl-N'-isopropyl-p-phenylenediamine.
9. The method for preparing ultra-low temperature resistant rubber according to claim 6, wherein: The rotation speed of the front roller of the mixing mill in step (4) is 15-17 r / min, and the rotation speed of the rear roller is 17-19 r / min.
10. The method for preparing ultra-low temperature resistant rubber according to claim 6, wherein: In step (5), the positive vulcanization time t90 of the compression vulcanization is 17-19 minutes, and the positive vulcanization time t90 is the time to reach 90% vulcanization degree; the total time of compression vulcanization is t90+1 minute to t90+3 minutes.
Citation Information
Patent Citations
Silicon rubber / polyurethane rubber composite hydraulic sealing gasket and preparation method thereof
CN103408944A
Silicone rubber / polyurethane thermoplastic vulcanized rubber and preparing method thereof
CN105924972A
Polyurethane / fluorosilicone rubber thermoplastic elastomer for wearable device and preparation method thereof
CN109265966A
High-efficiency, cold-resistant and crack-resistant cable material and preparation method thereof
CN110467757A
Environment-friendly thermoplastic silicone rubber elastomer and preparation method thereof
CN110903654A